Development of Technological, Pedagogical and Content Knowledge Based Learning Media - Amaliyah, Nurrohmatul (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2023)
Problems in education are very diverse, one of which is that students are lazy to read and do not understand how to draw the right conclusions so that this has an impact on the learning achievement of Indonesian language students in grade VI SDN Petojo Utara Complex, which is less than optimal, especially in making decisions in a paragraph. Therefore, it is necessary to have learning media that can assist in conveying material to students and support students' understanding in drawing conclusions from a paragraph, one of which is learning media.based on TPACK (Technological, Pedagogical, Content Knowledge). The research method used in this research is the ADDIE development research model which is a model that involves the stages of model development with five development steps/phases, including: Analysis, Design, Development or Production, Implementation or Delivery and Evaluations. The results showed that the development of TPACK-Based Learning Media was implemented at MI Pembangunan UIN Jakarta. The results of student assessments of the TPACK-based learning media development assessment obtained an average value of 4.7 close to strongly agreeing with the statements submitted. Student responses to the e-module varied, the majority of class 1D and 1G MI Pembangunan UIN gave a positive response. However, some students gave responses that were difficult to understand because they were not in accordance with the learning styles of students. Therefore, it is important for e-module developers to pay attention to the quality and characteristics of e-modules in order to generate positive responses from students.